A Physics-based Model of Hydrogen Bond Disruption in Cell Membranes Under Electric Fields (London Journal of Research In Science: Natural and Formal, 2025)
A physical model is presented for hydrogen bonding in an effort to better understand the impact of electric fields on hydrogen bonds in human cells. Using fundamental dielectric physics and hydrogen-bonding in cell membranes, the model indicates that little/no membrane degradation will occur for external electric fields of ? 200V/cm. The model also indicates that significant damage to the cell membrane will commence at external fields as low as 1kV/cm, strong and irreversible cell membrane degradation will occur at 10kV/cm, and catastrophic cell membrane damage will occur at 40kV/cm. Any cell membrane degradation (that permits water molecules to permeate the normally hydrophobic cell membrane layer) is shown to be particularly devastating for H-bond breakage. This work is important not only for determining the safe-levels of external electric field for humans but also the external field levels that impact the electroporation process where cancer cell membranes are purposely broken down with electric field.
Keywords: Aleurodicusrugioperculatus; Aspergillus spp.; host crops and symbiosis; GIS; territorial planning; spatial sampling; urban growth